High Dimensional Mass Cytometry Analysis Reveals Characteristics of the Immunosuppressive Microenvironment in Diffuse Astrocytomas - Fu, Weilun; Wang, Wenjing; Li, Hao; Jiao, Yuming; Weng, Jiancong; Huo, Ran; Yan, Zihan; Wang, Jie; Xu, Hongyuan; Wang, Shuo; Wang, Jiangfei; Chen, Dexi; et al. (Frontiers in Oncology, 2020)
The tumor immune microenvironment (TIME) plays a pivotal part in tumor development, progression, and prognosis. However, the characteristics of TIME in diffuse astrocytoma (DA) is still unclear. Leveraging Mass Cytometry with a panel of 33 markers, we analyzed the infiltrating immune cells from 10 DA and 4 oligodendroglioma (OG) tissues and provided a single-cell-resolution landscape of the intricate immune microenvironment. Our study profiled the composition of TIME in DA and confirms the presence of immune cells, such as glioma-associated microglia/macrophages (GAMs), CD8+ T cells, CD4+ T cells, regulatory T cells (Tregs) and natural killer cells. Increased percentages of PD-1+ CD8+ T cell, TIM-3+ CD4+ T cell subpopulations, Tregs and pro-tumor phenotype of GAMs substantially contribute to local immunosuppressive microenvironment in DA. DAs and OGs share similar composition of the immune cells, while the GAMs in DA exhibit more inhibitory characteristics than that of OG.